The state regional policy objects: economic law aspect - Тертишна, Лілія Сергіївна (Theory and practice of jurisprudence, 2017)
The article covers the research of the state regional policy objects requiring the economic law enforcement actions of the state. The state regional policy objects are divided into the primary – carrying both major and general qualities and minor — the segment objects. In terms of legislation there is no classification of the state regional policy objects requiring the economic law enforcement actions. The classification and systematization of state regional policy objects requiring the economic law enforcement actions will help to determine the complex and extent of the need of application of the economic law enforcement actions necessary for each of the named objects. Today, the uncertainty of such objects leads to a lack of efficiency in the implementation of the state regional policy: the complete list of such objects is not established, therefore the economic law enforcement actions are not established as well. It was found that for all state regional policy objects the universal are such economic law enforcement actions as a public-private partnership and special modes of management. The tripartite agreement between government, local government and business entity was defined as a model of public-private partnership that will be characteristic for such policy.